2011
DOI: 10.1523/jneurosci.4416-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila taoControls Mushroom Body Development and Ethanol-Stimulated Behavior throughpar-1

Abstract: In both mammalian and insect models of ethanol-induced behavior, low doses of ethanol stimulate locomotion. However, the mechanisms of the stimulant effects of ethanol on the CNS are mostly unknown. We have identified tao, encoding a serine-threonine kinase of the Ste20 family, as a gene necessary for ethanol-induced locomotor hyperactivity in Drosophila. Mutations in tao also affect behavioral responses to cocaine and nicotine, making flies resistant to the effects of both drugs. We show that tao function is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 39 publications
3
88
0
Order By: Relevance
“…S3e). These results strongly support the role of TAO2 in axon elongation in the mouse in vivo , as was previously reported in Drosophila 19 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S3e). These results strongly support the role of TAO2 in axon elongation in the mouse in vivo , as was previously reported in Drosophila 19 .…”
Section: Resultssupporting
confidence: 92%
“…1c). This pattern of TAO2 expression suggests that TAO2 may act as a coordinator of actin and microtubule dynamics 19 .…”
Section: Resultsmentioning
confidence: 92%
“…The mushroom bodies are structures involved in associative learning in flies (Shuai et al, 2010), and they undergo major reorganization and restructuring during pupal metamorphosis (Armstrong, de Belle, Wang, & Kaiser, 1998). Unlike some of the previously mentioned regulators of actin dynamics, Tao is required during development and not in the adult fly (King et al, 2011), indicating that the kinase is involved in setting up ethanol-responsive circuitry. Tao acts through the Jun N-terminal MAP kinase, JNK, to regulate ethanol-induced hyperactivity and brain morphology (Kapfhamer et al, 2012).…”
Section: Cell Adhesion and Structurementioning
confidence: 91%
“…Loss of Tao leads to a decrease in ethanol-induced hyperactivity in flies and also to morphological defects in the brain, including the mushroom III. GENE AND BEHAVIOR bodies (King et al, 2011). The mushroom bodies are structures involved in associative learning in flies (Shuai et al, 2010), and they undergo major reorganization and restructuring during pupal metamorphosis (Armstrong, de Belle, Wang, & Kaiser, 1998).…”
Section: Cell Adhesion and Structurementioning
confidence: 99%
“…In addition to ERK1/2, other MAPKs have also been found to regulate the acute effects of alcohol in flies. A Drosophila genetic screen revealed that a loss-offunction mutation of the Tao gene, encoding a putative MAP3K belonging to a subfamily of the sterile 20 protein (Ste20p) kinases, reduced alcohol-induced locomotor hyperactivity (King et al, 2011). There are three mammalian orthologs of Drosophila tao: TaoK1, TaoK2, and TaoK3.…”
Section: Acute Alcohol-induced Sedation and Rapid Tolerancementioning
confidence: 99%